Engineering Clostridium cellulovorans for highly selective n‐butanol production from cellulose in consolidated bioprocessing. Issue 7 (23rd April 2021) - Bao, Teng; Hou, Wenjie; Wu, Xuefeng; Lu, Li; Zhang, Xian; Yang, Shang‐Tian
Abstract: Cellulosic n ‐butanol from renewable lignocellulosic biomass has gained increased interest. Previously, we have engineered Clostridium cellulovorans, a cellulolytic acidogen, to overexpress the bifunctional butyraldehyde/butanol dehydrogenase gene adh E2 from C. acetobutylicum for n ‐butanol production from crystalline cellulose. However, butanol production by this engineered strain had a relatively low yield of approximately 0.22 g/g cellulose due to the coproduction of ethanol and acids. We hypothesized that strengthening the carbon flux through the central butyryl‐CoA biosynthesis pathway and increasing intracellular NADH availability in C. cellulovorans adh E2 would enhance n ‐butanol production. In this study, thiolase ( thl A CA ) from C. acetobutylicum and 3‐hydroxybutyryl‐CoA dehydrogenase ( hbd CT ) from C. tyrobutyricum were overexpressed in C. cellulovorans adh E2 to increase the flux from acetyl‐CoA to butyryl‐CoA. In addition, ferredoxin‐NAD(P) + oxidoreductase ( fnr ), which can regenerate the intracellular NAD(P)H and thus increase butanol biosynthesis, was also overexpressed. Metabolic flux analyses showed that mutants overexpressing these genes had a significantly increased carbon flux toward butyryl‐CoA, which resulted in increased production of butyrate and butanol. The addition of methyl viologen as an electron carrier in batch fermentation further directed more carbon flux towards n ‐butanol biosynthesis due to increased reducing equivalent or NADH. The engineered strain C. cellulovorans adh E2‐ fnr CA ‐ thl A CA ‐ hbd CT produced n ‐butanol from cellulose at a 50% higher yield (0.34 g/g), the highest ever obtained in batch fermentation by any known bacterial strain. The engineered C. cellulovorans is thus a promising host for n ‐butanol production from cellulosic biomass in consolidated bioprocessing. Abstract : Clostridium cellulovorans adh E2 was engineered to overexpress thiolase ( thl A CA from C. acetobutylicum ) and 3‐hydroxybutyryl‐CoA dehydrogenase ( hbd CT from C. tyrobutyricum ), which increased the carbon flux from acetyl‐CoA to butyryl‐CoA, and ferredoxin‐NAD(P) + oxidoreductase ( fnr ), which facilitated NADH regeneration. With methyl viologen (MV) as electron carrier, hydrogen production was inhibited and NAD(P)H availability further increased, which greatly enhanced butanol production from cellulose.